CLINICAL NEUROPATHY AND METFORMIN USE. TIME TO MONITOR VITAMIN B12? NEUROPATIA CLINICA: ¿METFORMINA ASOCIADA A DEFICIENCIA DE VITAMINA B12? - Paucar, Maria Fatima (2019)
Metformin is a first-line farm in the treatment of type 2 diabetes mellitus, but the results of its study are based on a deficit of vitamin B12. Research studies on the clinical neuropathy that can occur in people treated with Metformin with vitamin B12 deficiency.